The Relationship Between Neuroticism And Stress Levels Among Early Childhood Education Students At A University - Ibrahim, Nurul Nabila; Ramli, Azwidah Fariha Binti; Nahar Efairuz, Azeera Asyikin Binti; Khairun Nidzam, Hannah Balqis Binti (Selangor Humaniora Review, 2023)
It is crucial to investigate the decreasing quality of study performances and the level of stress among students. This is because psychological instability or neuroticism is associated with stress and affects the quality of studying and academic performance. The purpose of the study is to identify the relationship between neuroticism and stress levels in a sample of Early Childhood Education (ECE) students in Universiti Selangor (UNISEL). Neuroticism is a broad personality trait dimension that represents how distressing, frightening, and unsafe a person can perceive the world. Meanwhile, the stress level is any change that creates discomfort and is referred to as stress either physically, emotionally, or psychologically. In this study, quantitative data collection and correlational research were used, in which the data was collected via an online survey. We also used convenient sampling to collect data among the respondents. We measured the neuroticism level of participants using Eysenck’s Five-Factor Model and we also assessed participants’ levels of stress using the stress component of the Depression, Anxiety, and Stress Scale (DASS). The questionnaires were scored on a five Likert-scale rating. We analysed our variables using SPSS. Responses were analysed using reliability statistics of Cronbach’s Alpha. The results concluded that the Cronbach’s Alpha for the overall reliability of the pilot study is 0.810 where the instrument is concluded as reliable and can be accepted for the study. The result revealed that there is a significant positive relationship between the levels of neuroticism and stress among ECE students at UNISEL.